90.9k views
4 votes
?????evauate?????????

?????evauate?????????-example-1
User Jazzurro
by
5.7k points

2 Answers

1 vote

Answer:

2

Explanation:


{a}^(2) + 7a + 8

Substitute


a = - 6

in the above equation to get:


{( - 6)}^(2) + 7( - 6) + 8

Simplify:


36 + ( - 42) + 8


36 - 42 + 8


- 6 + 8


2

User Cheol
by
4.8k points
2 votes

Answer:

2

Explanation:

Substitute a = - 6 into the expression, that is

a² + 7a + 8

= (- 6)² + 7(- 6) + 8 = 36 - 42 + 8 = - 6 + 8 = 2

User Marcus Nunes
by
5.0k points